1985
DOI: 10.1111/j.1939-0025.1985.tb03441.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and foster care: Census data as predictors of placement variables.

Abstract: An epidemiological approach to foster care is presented, in which two separate data sets are used to analyze issues of ethnicity and child placement. A national probability sample and a large-city sample are drawn from the 1980 Office of Civil Rights ethnic survey and from the 1980 U.S. Census in order to test several hypotheses on ethnic differences predictive of time in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 2 publications
(3 reference statements)
2
18
0
Order By: Relevance
“…Three variables in the vignette were experimentally manipulated: race, SES of the foster care environment, and previous treatment; upon reading the vignette, social workers were asked to make a decision as to the proper placement of the child (community versus residential) and to rate the child and his emotional and environmental context using the Child and Adolescent Needs and Strengths (CANS). Prior research has suggested that both race/ethnicity and SES can influence professionals' placement decision-making in a child welfare setting (e.g., Finch et al, 1986;Glisson et al, 2000;Jenkins & Diamond, 1985;Lindsey, 1991;McMurtry & Lie, 1992); however, to date, no study has used an experimental vignette procedure to examine the effects of these variables on the decision to admit a child to a residential treatment center versus maintaining him or her in a community setting.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Three variables in the vignette were experimentally manipulated: race, SES of the foster care environment, and previous treatment; upon reading the vignette, social workers were asked to make a decision as to the proper placement of the child (community versus residential) and to rate the child and his emotional and environmental context using the Child and Adolescent Needs and Strengths (CANS). Prior research has suggested that both race/ethnicity and SES can influence professionals' placement decision-making in a child welfare setting (e.g., Finch et al, 1986;Glisson et al, 2000;Jenkins & Diamond, 1985;Lindsey, 1991;McMurtry & Lie, 1992); however, to date, no study has used an experimental vignette procedure to examine the effects of these variables on the decision to admit a child to a residential treatment center versus maintaining him or her in a community setting.…”
Section: Discussionmentioning
confidence: 98%
“…However, research indicates that non-clinical factors such as race/ethnicity and socioeconomic status (SES) may in fact influence the placement decision-making process. For example, prior research has indicated that African-American or non-white children are more likely to be in out-of-home care for longer periods of time compared to Caucasian children (Finch, Fanshl, & Grundy, 1986;Glisson, Bailey, & Post, 2000;Jenkins & Diamond, 1985;McMurtry & Lie, 1992;Olsen, 1982), less likely to be adopted (Finch et al, 1986) and more likely to be considered for treatment foster care, a more intensive alternative to other community placements (Courtney, 1998). Though other studies have not found significant effects of race on decisions regarding return to biological parent versus out-of-home care (Zuravin & DePanfilis, 1997) or on time in state custody (see Glisson et al, 2000), on the whole, race appears to be a significant non-clinical factor in placement decisions.…”
Section: Introductionmentioning
confidence: 98%
“…The most recent figures on participants in substitute care indicate that African Americans represent about 60 percent of foster care youth in urban areas (Jenkins & Diamond, 1985;Shyne & Schroeder 1978). This group is judged to be at risk based on the premise that foster care placements alter the developmental pathways that typically lead to self-sufficiency among adolescents.…”
Section: Seventy-six Africanmentioning
confidence: 97%
“…Characteristics such as the median income and the rural/urban nature of a community are important to children's services because they represent differences in resources, cultural norms and community structure that affect judicial decisions and service availability (Glisson et aL, 2000). Several studies of duration of care reported that children in more rural counties, where there may be even fewer resources, were less likely to leave custody than similar children in more urban counties (Benedict & White, 1991;Berrick et aI., 1997;Courtney & Wong, 1996;Glisson et aL, 2000;Goerge, 1990;Jenkins & Diamond, 1985;Martin et aL, 2002;Potter & Klein-Rothschild, 2002). Goerge (1990) reported that children in rural areas experienced decreasing probabilities of reunification while children in urban settings experienced more constant probability of reunification.…”
Section: Amount Spent On Child's Placementmentioning
confidence: 99%
“…Numerous studies have shown that minority children, particularly African American children, experience negative permanency outcomes (Albers et aI., 1983;Barth, 1997;Barth et aI., 1986;Courtney, 1994;Courtney & Wong, 1996;Glisson, Bailey, & Post, 2000;Goerge, 1990;Goerge et aI., 1994;Horawitz et aI., 1994;Jenkins, 1967;Jenkins & Diamond, 1985;Jenkins et aI., 1983;Jones, 1998;Kemp & Bodonyi, 2000;Kemp & Bodinyi, 2002;McMurty & Lie, 1992;Olsen, 1082;Potter & Klein-Rothschild, 2002;Schmidt-Tieszen & McDonald, 1998;Schwartz et al,1994;Seaberg & Tolley, 1986, Wells & Guo, 1999White et aI., 1996;Wulczyn, 1994;Wulczyn et aI., 2000). Most of these studies were conducted prior to the implementation of permanency planning or mandated shortened time frames for obtaining permanency for children in foster care.…”
Section: Racementioning
confidence: 99%